Poligami Dalam Perspektif Hukum Islam dan Undang-Undang Perkawinan Di Indonesia - Daffa Akmal Manurung; M. Hafizh Khairi; M. Hafizh Maulana; Syahrul Agil; Ananda Prayoga (Tabayyun : Journal Of Islamic Studies, 2023)
Polygamy is the practice of a man marrying more than one woman simultaneously. The foundation of polygamy in Indonesia, apart from marriage law, also comes from Islamic law. This article was written in order to examine how marriage law in Indonesia and Islamic law regulate the practice of polygamy. Even though polygamy is permitted in Islamic law, there are several things that must be considered, such as justice and others. Meanwhile, in Indonesian marriage law, regulations regarding polygamy are strictly regulated with various requirements that must be met to carry out polygamy.